2012
DOI: 10.1159/000342992
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic and Morphometric Evaluation of the Nasal and Pulmonary Airways of Cats with Experimentally Induced Asthma

Abstract: Background: Allergic rhinitis frequently occurs as a comorbid condition in asthmatic people, suggesting that the upper and lower airways may be immunologically linked. Our research group has developed an experimental aeroallergen model of asthma in cats. We hypothesized that aeroallergen sensitization and challenge would induce morphologic changes in the nasal airways of cats that mimic those observed in the bronchial airways. Methods: Five mixed breed cats were sensitized to Bermuda grass allergen and then se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 98 publications
(56 reference statements)
0
6
2
1
Order By: Relevance
“…In healthy dogs, NALT has not been identified and epithelial MHC class II expression is rare (Peeters et al, 2005b), while both of these characteristics are common in horses (Banks et al, 1999;Liebler-Tenorio and Pabst, 2006;Quintana et al, 2011) in the absence of respiratory disease. NALT has been previously reported in cats in the absence of upper respiratory tract disease (Venema et al, 2013). In the present study NALT was not identified and MHCII expression was also common in cats in the absence of URT disease.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In healthy dogs, NALT has not been identified and epithelial MHC class II expression is rare (Peeters et al, 2005b), while both of these characteristics are common in horses (Banks et al, 1999;Liebler-Tenorio and Pabst, 2006;Quintana et al, 2011) in the absence of respiratory disease. NALT has been previously reported in cats in the absence of upper respiratory tract disease (Venema et al, 2013). In the present study NALT was not identified and MHCII expression was also common in cats in the absence of URT disease.…”
Section: Discussioncontrasting
confidence: 60%
“…In the present study NALT was not identified and MHCII expression was also common in cats in the absence of URT disease. The absence of detectable NALT in the present study is likely due to anatomical differences in sampling, since NALT was previously detected in the caudal nasal cavity and nasopharyngeal meatus, which were not sampled in the current study (Venema et al, 2013).…”
Section: Discussioncontrasting
confidence: 53%
“…One previous study 3 found upper respiratory tract signs in 25% of cats diagnosed with asthma or bronchitis whereas another 13 reported nasal discharge more often in cats with chronic bronchitis than in those with asthma. An association of asthma with upper respiratory viruses has been noted in children, 37,38 and nasal airways in cats with experimentally induced asthma were noted to have eosinophilic infiltration in the absence of clinical signs 39 . Whether this finding was related to the method of hypersensitization via aerosolized allergen in the experimental study or represented a distinct response of the upper respiratory epithelium in those cats is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Cats could have had two unrelated diseases leading to rhinitis and lower airway disease. Another possibility is the “united airways theory” which in humans and an experimental model of feline allergic asthma suggests an immunologic link to explain the comorbid conditions of rhinitis and allergic asthma . A third possibility is postnasal drip leading to chronic aspiration and chronic bronchitis with potential bronchial plugging.…”
Section: Discussionmentioning
confidence: 99%